2018
DOI: 10.11158/saa.23.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of salivary proteins from the facultative symbiont-infected and uninfected Tetranychus truncatus

Abstract: Salivary proteins of herbivorous insects play a central role in plant-insect interactions. Spider mite Tetranychus truncatus is a polyphagous agricultural pest harboring various bacterial symbionts. However, whether endosymbionts infection in spider mite alters the host saliva protein remains largely unknown. Here, by using shotgun LC-MS/MS analysis, we identified and characterized the components of saliva in Wolbachia-Spiroplasma infected and uninfected T. truncatus. In total, 177 putative salivary proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Recently, the influence of microorganisms on saliva secretions has attracted increasing attention (Chaudhary et al, ; Zhu et al, ). Planthoppers harbor many endosymbionts and are an important vector in viral transmission (Xue et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the influence of microorganisms on saliva secretions has attracted increasing attention (Chaudhary et al, ; Zhu et al, ). Planthoppers harbor many endosymbionts and are an important vector in viral transmission (Xue et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous proteome studies on spider mites identified about 90 and 177 putative SGPs from T. urticae and Tetranychus truncates (Jonckheere et al ., ; Zhu et al ., ), neither Tet1 nor Tet2 was listed among them. However, we observed that Tet1 is expressed predominantly in the anterior podocephalic salivary glands, possibly together with the silk glands, of T. urticae , implying that Tet1 is secreted outside of the body.…”
Section: Discussionmentioning
confidence: 99%
“…After transient overexpression, PDI1 orthologs strongly induce ROS burst and plant cell death. Classical PDIs have also been detected in saliva proteomes of other piercing-sucking insects such as aphids ( Carolan et al, 2011 ; Van Bel and Will, 2016 ) and spider mites ( Zhu et al, 2018 ). For this reason, PDIs may have a common interaction mechanism between various herbivorous insects and their plant hosts and may be able to induce broad-spectrum insect resistance.…”
Section: Discussionmentioning
confidence: 99%